Effect of kaempferol ingestion on physical activity and sleep quality: a double-blind, placebo-controlled, randomized, crossover trial - Ikeda, Yasutaka; Gotoh-Katoh, Aina; Okada, Shinpei; Handa, Shuichi; Sato, Teruyuki; Mizokami, Tsubasa; Saito, Bungo (Frontiers in Nutrition, 2024)
Background Kaempferol (KMP), a flavonoid in edible plants, exhibits diverse pharmacological effects. Growing body of evidence associates extended lifespan with physical activity (PA) and sleep, but KMP’s impact on these behaviors is unclear. This double-blind, placebo-controlled, crossover trial assessed KMP’s effects on PA and sleep. Methods A total of 33 city workers (17 males and 16 females) participated in this study. They were randomly assigned to take either 10 mg of KMP or placebo for 2 weeks in the order allocated, with a 7-day washout period in between. All participants wore an accelerometer-based wearable device (Fitbit Charge 4), which monitored daily PA, heart rate (HR), and HR variability during sleep. Results The duration of wearing the device was 23.73 ± 0.04 h/day. HR decreased in each PA level, and the mean daily step count and distance covered increased significantly during KMP intake compared to placebo. The outing rate, number of trips, number of recreational activities, and time spent in recreation on weekends increased. Sleep quality improved following KMP intake. The decrease in HR and increase in RMSSD may be important in mediating the effects of these KMPs. Conclusion KMP leads to behavioral changes that subsequently improve sleep quality and potentially improve long-term quality of life. Clinical Trial Registration https://center6.umin.ac.jp/cgi-open-bin/ctr_e/ctr_view.cgi?recptno=R000048447, UMIN000042438.